A Repeatable Epitaxial Lift‐Off Process from a Single GaAs Substrate for Low‐Cost and High‐Efficiency III‐V Solar Cells. Issue 16 (1st July 2014) - Choi, Wonjung; Kim, Chang Zoo; Kim, Chang Su; Heo, Wooseok; Joo, Taiha; Ryu, Seung Yoon; Kim, Hogyoung; Kim, Hongjoon; Kang, Ho Kwan; Jo, Sungjin
<x xml:space="preserve">Abstract</x> The effects of epitaxial materials and solar cell design on the performance of solar cells grown by the multilayer approach are investigated. The novel solar cell structure with a p‐on‐n type configuration suggested exhibits improved uniformity in the photovoltaic performance because of the suppression of Zn diffusion. This approach provides routes to achieve further improvements and acts as a guideline for the commercialization of the multilayer technique. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>